Study and Investigation: Interpretation Surat Ibrahim for Al-Fadhel Al-Yemeni in His Note Durar Al-Sadaf Fi Hal Oqad Al-Kashaf - Maqbol, Omar Fuaini Omar (Journal of Islamic Sciences, 2023)
Many scholars of Yemen have excelled in the interpretation throughout the ages, and among them is the scholar known as Al-Fadhel Al-Yemeni, whose his note worked as Durar Al-Sadaf Fi Hal Oqad Al-Kashaf. It is one of the broadest note of Al-Kashaf. The research aims to introduce of the Al-Fadhel Al-Yemeni, and his note to Durar Al-Sadaf, with investigation of Surat Ibrahim. In translating the author and introducing his book, the research used the descriptive and inductive approach to collect what related to his life and his note. Then, the researcher presented an example of investigation for Surat Ibrahim in full, to show the method of investigation that it followed in terms of comparing copies and proving differences and falls, and what is related to the investigation of attribution, graduation, to hadiths, attribution of sayings, analysis of opinions, and attribution of evidence and texts to their sources and commenting when needed. The researcher concluded that the note Durar Al-Sdaf was characterized by its treatment of difficult issues in the linguistic and rhetorical aspects through poetic evidence and grammatical rules with the accuracy of inference, abundance of understanding, and good editing. The researcher recommended by the reflections of Al-Fadhel Al-Yemeni virtuous Ali Al-Zamakhshari in his note Durar Al-Sdaf and studying them as an independent scientific study.